THE ROLE OF DRILLING TECHNIQUE TOWARDS STUDENTS’ SPEAKING SKILL OF SECOND GRADE OF ELEMENTARY SCHOOL STUDENTS - Prihamdani, Depi; Suparman, Tarpan; Sukma, Andhi (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to analyze the role of drilling technique towards student’s speaking skill. In learning a language, particularly in learning English, speaking skill is one of the four basic competences that the students should gain well because it takes an important role in communication. So, that is why the researcher was interested in conducting research on The Role of Drilling Technique towards Students’ Speaking Skill of Second Grade of Elementary Students. The research method of this research was quantitative. So, in order to get a complete and concrete data, the researcher conducted an experiment by teaching speaking on the second grade students of elementary school. The researcher took 24 students for the sample. They are divided in two classes; each class consists of 12 students. The experimental class was taught by using drilling technique while the control class was taught by using conventional technique. The researcher used pre-test and post-test to measure the significant difference of teaching speaking using drilling technique and teaching speaking using conventional technique. In the test, it consists of 10 questions. The researcher gave same questions for both of classes. Then the results of those tests were used to analyze whether teaching speaking using drilling technique is effective or not. The gathered data were analyzed by using statistical analysis. The researcher used t-test formula. Based on the data, the mean score of experimental class was higher than the mean score of control class (8,12 > 6,62). Besides that the result of t-test was higher than t-table (2,14 > 1,717). The results of the analysis showed that drilling technique improves the second grade students’ speaking skill of elementary school.